Effect of MTA and Portland Cement on Fracture Resistance of Dentin - Maryam Forghani; Maryam Bidar; Fatemeh Shahrami; Mahmoud Bagheri; Maryam Mohammadi; Niloufar Attaran Mashhadi (Tabriz University of Medical Sciences, 2013)
Background and aims. It is important to evaluate the effects of endodontic materials on tooth structures to avoid endodontic treatment failure. The aim of the present study was to investigate the effect of mineral trioxide aggregates (MTA) and Portland cement (PC) on fracture resistance of dentin. Materials and methods. Thirty-six freshly extracted human single-rooted premolar teeth were selected. The crowns were removed and the roots were randomly divided into two experimental groups and one control group. The root samples were longitudinally divided into two halves and a dentin bar (2×2×10 mm) was cut from each root section for short-term (2 weeks) and long-term (12 weeks) evaluations. The root sections in the experimental groups were exposed to MTA or PC, while keeping the control group specimens in physiologic saline. The fracture resistance of each specimen was measured using an Instron testing machine. The results were statistically analyzed using ANOVA, a post hoc Tukey test and paired ttest at 5% significance level. Results. The fracture resistance of MTA-treated specimens significantly increased between 2 and 12 weeks (P<0.05). After 12 weeks, MTA-treated specimens had the highest fracture resistance. In the PC group, the fracture resistance of specimens did not change significantly over time (P>0.05). Conclusion. The results showed that MTA increased the fracture resistance of root dentin, while PC had no significant effect on dentin fracture resistance.